Position of Regional Development Banks as Regional Owned Enterprises - Marenda, Radhy Anugrah; Neltje, Jeane (Green Publisher Indonesia, 2023)
Regional-owned enterprise is a business entity established by a local government with the purpose of increasing local own-source revenue, where one of the commonly found regional-owned enterprises is a regional-owned enterprise engaged in financial service institutions. The problem that arises for regional owned enterprises engaged in financial service institutions is the overlapping provisions of the laws and regulations that govern them, so this causes legal uncertainty over the position of the Bank. So, to find out the legal certainty of the position of regional development banks, normative legal research methods are used, namely research that uses a statutory approach where the research is carried out on the provisions of the legal aspects of regional-owned enterprises, and aspects of banking law, including the legal aspects regarding limited liability companies.